The role of courtship song in female mate choice in South American Cactophilic Drosophila - Iglesias, Patricia Paola (2017)
Courtship songs have undergone a spectacular diversification in the Drosophila buzzatii cluster. Accordingly, it has been suggested that sexual selection has played a significant role in promoting rapid diversification, reproductive isolation and speciation. However, there is no direct evidence (i.e., song playback experiments with wingless males) supporting this tenet. Moreover, several studies have showed that the courtship song in the genus Drosophila is not always used in female mate choice decisions, nor plays the same role when itis taken into account. In this vein, we use an approach that combines manipulative and playback experiments to explore the importance and the role of courtship song in female mate choice in four species of the D. buzzatii cluster and one species of the closely related D. martensis cluster for outgroup comparison. We also investigate the importance of courtship song in sexual isolation in sympatry between the only semi-cosmopolitan species, D. buzzatii, and the other species of the D. buzzatii cluster. Our study revealed that the courtship song is used by females of the D. buzzatii cluster as a criterion for male acceptance or influences the speed with which males are chosen. In contrast, we showed that this characteristic is not shared by D. venezolana, the representative species of the D. martensis cluster. We also found that the studied species of the D. buzzatii cluster differ in the role that conspecific and heterospecific songs have in female mate choice and in sexual isolation. Our findings support the hypothesis that divergence in female preferences for courtship songs has played a significant role in promoting rapid diversification and reproductive isolation in the D. buzzatii cluster. However, evidence from D. venezolana suggests that the use of the courtship song in female mate choice is not a conserved feature in the D. buzzatii complex.